Eye-Tracking in sport psychology - Grushko, A.; Leonov, S.; Veraksa, A. (Advances in sports research, 2015)
The chapter presents the results of the research aimed at eye-tracking technology implementation in training of professional athletes. Particular attention is paid to the focus of attention at performing technical actions, visual search strategies, pupil diameter (as an indicator of cognitive load), number and duration of saccades, fixations, blinks (Vickers 2001, Velichkovsky 2006, Barabanschikov, Zhegallo 2013). The advantages of this method of psychological preparation of athletes are described: high ecological validity; the ability to "see through the eyes of an athlete" current training or competitive task for subsequent analysis and correction of his/her actions; the use of eye-tracking technology not only as a means of diagnostics, but also as a training method of athletes. The directions of psychological preparation of athletes by means of eye-tracking technology usage with hard-coordinated actions implementation are presented (Panchuk, Vickers 2006, Menshikova et al. 2014). In particular combination of eye-tracking with virtual reality reveals gaze behavior peculiarities of athletes vs untrained subjects in a dynamic 3D visual stimulation. It was shown that professional figure skaters use oculomotor nystagmus mechanism more active in order to compensate the vestibular disorders.See discussions, stats, and author profiles for this publication at: https://www.researchgate.net/publication/284030861